Therapeutic electrophysical agents : evidence behind practice / Alain-Yvan Bélanger, PhD, PT, Retired Professor, Laval University, Canada, owner and consultant, Physiométrix Inc - Bélanger, Alain
Therapeutic electrophysical agents in health care -- Toward a practice based on evidence -- Soft-tissue healing process -- Pain following soft-tissue pathology -- Purchase, electrical safety, and maintenance -- Therapeutic spectrum, selection and indication -- Thermotherapy -- Cryotherapy -- Hydrotherapy -- Shortwave diathermy -- Low-level laser therapy -- Ultraviolet -- Neuromuscular electrical stimulation -- Transcutaneous electrical nerve stimulation -- Electrical stimulation for tissue healing and repair -- Iontophoresis -- Spinal traction -- Limb compression -- Continuous passive motion -- Ultrasound -- Extracorporeal shock wave therapy.